Colour and E. Coli Removals by Riverbed Filtration – A Physical Modelling Study at Different Filter Bed Depths and Inflow Rates - Ghani, Mastura (International Journal of Integrated Engineering, 2019)
Riverbed filtration system (RBeF) is a simple, efficient and cost-effective alternative method of extracting water for drinking water purpose. The contaminants present in the surface water were attenuated biochemically where the aquifer acts as a natural filter. This study involved a physical model work for riverbed filtration (RBeF), where the depth of filter media and the flow rate of surface water were manipulated to improve the removal percentage of true colour and E. Coli (media depth: 60 and 90 cm, flow rate: 1, 3 and 5 L/min). River water samples from Lubok Buntar, Kedah were used to simulate the effectiveness of RBeF for colour and E. Coli removal. Readings were tested at the inlet and outlet of the filter with specified flow rates. Results from the physical model study showed the colour and E. Coli removal increased as the media depth increased from 60 to 90 cm, from 23-57.28% to 14.82-78.45% (p-value 0.008) and 69.45-98.34% to 76.15-99.69% (p-value 0.027), respectively. Besides that, from the study, results showed that the colour and E. Coli removal were not significantly affected by the flow rate.